Safety and immunogenicity of a highly attenuated rVSVN4CT1-EBOVGP1 Ebola virus vaccine: a randomised, double-blind, placebo-controlled, phase 1 clinical trial. Issue 4 (April 2020) - Clarke, David K; Xu, Rong; Matassov, Demetrius; Latham, Theresa E; Ota-Setlik, Ayuko; Gerardi, Cheryl S; Luckay, Amara; Witko, Susan E; Hermida, Luz; Higgins, Terry; Tremblay, Marc; Sciotto-Brown, Susan; et al.
Summary: Background: The safety and immunogenicity of a highly attenuated recombinant vesicular stomatitis virus (rVSV) expressing HIV-1 gag (rVSVN4CT1-HIV-1gag1) was shown in previous phase 1 clinical studies. An rVSV vector expressing Ebola virus glycoprotein (EBOV-GP) in place of HIV-1 gag (rVSVN4CT1-EBOVGP1) showed single-dose protection from lethal challenge with low passage Ebola virus in non-human primates. We aimed to evaluate the safety and immunogenicity of the rVSVN4CT1-EBOVGP1 vaccine in healthy adults. Methods: We did a randomised double-blind, placebo-controlled, phase 1 dose-escalation study at a single clinical site (Optimal Research) in Melbourne, FL, USA. Eligible participants were healthy men and non-pregnant women aged 18–60 years, with a body-mass index (BMI) of less than 40 kg/m 2, no history of filovirus infection, VSV infection, or receipt of rVSV in previous studies, and who had not visited regions where Ebola virus outbreaks have occurred. Three cohorts were enrolled to assess a low (2·5 × 10 4 plaque forming units [PFU]), intermediate (2 × 10 5 PFU), or high dose (1·8 × 10 6 PFU) of the vaccine. Participants within each cohort were randomly allocated (10:3) to receive vaccine or placebo by intramuscular injection in a homologous prime and boost regimen, with 4 weeks between doses. All syringes were masked with syringe sleeves; participants and study site staff were not blinded to dose level but were blinded to active vaccine and placebo. The primary outcomes were safety and tolerability; immunogenicity, assessed as GP-specific humoral immune response (at 2 weeks after each dose) and cellular immune response (at 1 and 2 weeks after each dose), was a secondary outcome. All randomised participants were included in primary and safety analyses. This trial is registered with ClinicalTrials.gov, NCT02718469 . Findings: Between Dec 22, 2015, and Sept 15, 2016, 39 individuals (18 [46%] men and 21 [54%] women, mean age 51 years [SD 10]) were enrolled, with ten participants receiving the vaccine and three participants receiving placebo in each of three cohorts. One participant in the intermediate dose cohort was withdrawn from the study because of a diagnosis of invasive ductal breast carcinoma 24 days after the first vaccination, which was considered unrelated to the vaccine. No severe adverse events were observed. Solicited local adverse events occurred in ten (26%) of 39 participants after the first dose and nine (24%) of 38 participants after the second dose; the events lasted 3 days or less, were predominantly injection site tenderness (17 events) and injection site pain (ten events), and were either mild (19 events) or moderate (ten events) in intensity. Systemic adverse events occurred in 13 (33%) of 39 participants after the first dose and eight (21%) of 38 participants after the second dose; the events were mild (45 events) or moderate (11 events) in severity, and the most common events were malaise or fatigue (13 events) and headache (12 events). Arthritis and maculopapular, vesicular, or purpuric rash distal to the vaccination site(s) were not reported. A GP-specific IgG response was detected in all vaccine recipients after two doses (and IgG response frequency was 100% after a single high dose), and an Ebola virus neutralising response was detected in 100% of participants in the high-dose cohort. Interpretation: The rVSVN4CT1-EBOVGP1 vaccine was well tolerated at all dose levels tested and was immunogenic despite a high degree of attenuation. The combined safety and immunogenicity profile of the rVSVN4CT1-EBOVGP1 vaccine vector support phase 1–2 clinical evaluation. Funding: US Department of Defense Joint Program Executive Office for Chemical, Biological, Radiological and Nuclear Defense: Joint Project Manager for Chemical, Biological, Radiological and Nuclear Medical.